Exploring the Determinants of Sustainability in Ornamental Fisheries Startups: a Case Study on PT. Neptune Aquatic Marine - Ellyas Ellyas; Gede Sri Darma (Green Publisher Indonesia, 2025)
This study explores the resilience and sustainability of the ornamental fisheries industry, particularly focusing on PT. Neptune Aquatic Marine. Despite the challenges posed by the COVID-19 pandemic, this sector has shown remarkable adaptability and growth. The research utilizes qualitative methods, including case studies and literature reviews, to analyze the economic impact and strategies employed by the company. Data were collected through interviews and secondary sources, allowing for a comprehensive examination of internal and external factors influencing the industry. The findings indicate that improving human resource quality and innovation in products and services are critical for overcoming threats and leveraging opportunities in the market. The study emphasizes the importance of sustainability practices to ensure the long-term viability of ornamental fisheries.